How the Impact of ENSO Events on the Indonesian Throughflow and Interannual Variability of Circulation in the Halmahera Sea - Lubis, Muhammad Zainuddin; Dwinovantyo, Angga; Batara, B.; Kausarian, Husnul; Hidayat, Syarief; Priatna, Asep; Simanjuntak, Andrean V.H.; Ansari, Kutubuddin; Jamjareegulgarn, Punyawi (My University, 2026)
This study investigates the influence of El Niño–Southern Oscillation (ENSO) on the Indonesian Throughflow (ITF) in the Halmahera Sea (HS) during 2013–2023. Although ITF variability has been widely studied, the response of the HS to different ENSO phases remains insufficiently understood. Using a validated CROCO model, we quantified changes in HS throughflow and associated oceanographic conditions under El Niño and La Niña events. EOF analysis of sea surface height (SSH), meridional velocity, and salinity revealed dominant modes explaining more than 50% of the total variance and exhibiting clear ENSO-related variability. During El Niño events, ITF transport weakened substantially, with volume transport becoming less negative from − 4.0 ± 2.0 Sv to − 1.5 ± 1.5 Sv in the upper layer (0–100 m) and from − 5.0 ± 2.5 Sv to − 2.0 ± 2.0 Sv in the intermediate layer (0–400 m). These conditions were associated with a shallower thermocline, lower sea surface temperatures (25.5–26.0°C), and reduced surface salinity (34.74 PSU). In contrast, La Niña events strengthened the ITF, with transport reaching −7.0 ± 1.5 Sv in the upper layer and −7.0 ± 2.0 Sv in the intermediate layer, accompanied by a deeper thermocline and higher SSTs (29.8–30.42°C). The results suggest that ENSO-related variability in the HS is associated with coupled changes in thermocline structure, SSH gradients, and salinity, highlighting the importance of the HS in regulating ITF transport variability.
Keywords: El Niño–Southern Oscillation (ENSO); Halmahera Sea; ocean circulation; Indonesian Throughflow (ITF); Sea surface height; Thermocline variability; Volume transport